Antimicrobial use and antimicrobial resistance in Enterobacterales and Enterococcus faecium: a time series analysis. (February 2022) - O'Riordan, F.; Shiely, F.; Byrne, S.; O'Brien, D.; Ronayne, A.; Fleming, A.
Summary: Background: Irish and European antimicrobial resistance (AMR) surveillance data have highlighted increasing AMR in Enterobacterales and vancomycin resistance in Enterococcus faecium (VRE). Antimicrobial consumption (AC) in Irish hospital settings is also increasing. Methods: A retrospective time series analysis (TSA) was conducted to evaluate the trends and possible relationship between AC of selected antimicrobials and AMR in Enterobacterales and vancomycin resistance in E. faecium, from January 2017 to December 2020. Results: Increased AC was seen with ceftriaxone ( P = 0.0006), piperacillin/tazobactam ( P = 0.03) and meropenem ( P = 0.054), while ciprofloxacin and gentamicin use trended downwards. AMR rates in Escherichia coli, Klebsiella pneumoniae and other Enterobacterales were largely stable or decreasing, an increase in ertapenem resistance in the latter from 0.58% in 2017 to 5.19% in 2020 ( P = 0.003) being the main concern. The proportion of E. faecium that was VRE did not changed significantly (64% in 2017; 53% in 2020, P = 0.1). TSA identified a correlation between piperacillin/tazobactam use and the decreasing rate of ceftriaxone resistance in E. coli . Conclusion: Our data suggest that the hospital antimicrobial stewardship programme is largely containing, but not reducing AMR in key nosocomial pathogens. An increase in AC following the COVID-19 pandemic appears as yet to have had no impact on AMR rates.